Advances in Antiviral Material Development. Issue 9 (18th September 2020) - Liang, Lili; Ahamed, Ashiq; Ge, Liya; Fu, Xiaoxu; Lisak, Grzegorz
Abstract: The rise in human pandemics demands prudent approaches in antiviral material development for disease prevention and treatment by effective protective equipment and therapeutic strategies. However, the current state of the antiviral materials research is predominantly aligned towards drug development and its related areas, catering to the field of pharmaceutical technology. This Review distinguishes the research advances in terms of innovative materials exhibiting antiviral activities that take advantage of fast‐developing nanotechnology and biopolymer technology. Essential concepts of antiviral principles and underlying mechanisms are illustrated, followed by detailed descriptions of novel antiviral materials including inorganic nanomaterials, organic nanomaterials, and biopolymers. The biomedical applications of the antiviral materials are also elaborated based on the specific categorization. Challenges and future prospects are discussed to facilitate the research and development of protective solutions and curative treatments. Abstract : Biomedical applications : In this Review, the current state of antiviral materials research is summarized, categorized, and discussed. It distinguishes the research advances in the development of drug carriers, drug delivery systems, nanoparticles, biopolymers and protective equipment as therapeutic agents or protective equipment against virus infections.